2023
DOI: 10.3390/membranes13030303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compression and Porosity Gradients on Two-Phase Behavior in Gas Diffusion Layer of Proton Exchange Membrane Fuel Cells

Abstract: Water management within the gas diffusion layer (GDL) plays an important role in the performance of the proton exchange membrane fuel cell (PEMFC) and its reliability. The compression of the gas diffusion layer during fabrication and assembly has a significant impact on the mass transport, and the porosity gradient design of the gas diffusion layer is an essential way to improve water management. In this paper, the two-dimensional lattice Boltzmann method (LBM) is applied to investigate the two-phase behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…w adjusts the interaction forces between fluid and solid. More details of the multi-phase LB model adopted in this paper can be found in our previous work [ 44 ], and the accuracy has also been validated.…”
Section: Multi-phase Lb Modelmentioning
confidence: 99%
“…w adjusts the interaction forces between fluid and solid. More details of the multi-phase LB model adopted in this paper can be found in our previous work [ 44 ], and the accuracy has also been validated.…”
Section: Multi-phase Lb Modelmentioning
confidence: 99%
“…Additionally, it has been found that the inhomogeneous porosity distribution has a prominent impact on the liquid water behavior inside GDL [32,40]. Both experiments [41][42][43] and models [44][45][46][47] demonstrated that the gradient structure facilitates water transport and thus enhances output performance. Ko et al [43] experimentally observed that the porosity gradient significantly promoted water drainage, and the output performance was also advanced by comparing the polarization curves.…”
Section: Introductionmentioning
confidence: 95%